2015
DOI: 10.1097/cej.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

A birth cohort analysis of the incidence of adenocarcinoma of the uterine cervix in the USA

Abstract: Objectives We investigated the incidence trends for adenocarcinoma (AC) of the cervix among the 20-44 age group in the United States and compared the observed birth cohort incidence patterns with the changing patterns of exposure to potential risk factors associated with AC of the cervix, such as infection with human papillomavirus (HPV), use of diethylstilbestrol (DES), obesity, and use of oral contraceptives. Methods Using data from the National Cancer Institute's Surveillance, Epidemiology, and End Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…CIN3: cervical intraepithelial neoplasia grade 3, AIS: adenocarcinoma in situ Cancer Causes Control our study, the largest reductions were seen in women [44 years. The results for adenocarcinoma from other developed countries are conflicting, some studies reporting increasing incidence trends [2,3,6,7] and others showing constant or decreasing trends in recent years [8][9][10]. For example, in the USA, Adegoke et al [3] reported increasing incidence of adenocarcinoma among white women from 1.1 to 1.6 per 100,000 women-years between 1973-1975 and 2006-2007, corresponding to an annual increase of 3.6 %.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…CIN3: cervical intraepithelial neoplasia grade 3, AIS: adenocarcinoma in situ Cancer Causes Control our study, the largest reductions were seen in women [44 years. The results for adenocarcinoma from other developed countries are conflicting, some studies reporting increasing incidence trends [2,3,6,7] and others showing constant or decreasing trends in recent years [8][9][10]. For example, in the USA, Adegoke et al [3] reported increasing incidence of adenocarcinoma among white women from 1.1 to 1.6 per 100,000 women-years between 1973-1975 and 2006-2007, corresponding to an annual increase of 3.6 %.…”
Section: Discussionmentioning
confidence: 91%
“…& Susanne K. Kjaer susanne@cancer.dk some developed countries, including Denmark [3,[5][6][7], although not in all [8][9][10]. In the late 1960s, the Nordic countries were some of the first to introduce organized cervical cancer screening [11].…”
Section: Introductionmentioning
confidence: 98%
“…This finding is important, as HPV18associated lesions (particularly endocervical or glandular lesions) tend to be more difficult to detect by cytology alone and are becoming increasingly prevalent. [35][36][37] Khan et al previously demonstrated the high oncogenic potential of HPV16/18 in a 10-year cohort of women in the USA, noting that HPV-based cervical screening distinguishing HPV16/18 from other oncogenic genotypes could serve to identify HPV1 women most likely to progress to meaningful disease, while more appropriately managing women testing positive for other oncogenic genotypes. 10 Indeed, our data suggest that targeted or selective genotype-specific HPV testing could provide an important improvement in the positive predictive value of HPV-based screening.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, an increase in BMI has been associated with a higher risk of developing cervical adenocarcinoma. 34 , 35 Additionally, persistent cervical infection by high‐risk HPV strains is favored in obese women presenting vaginal dysbiosis, which is characterized by an increase in microbial diversity that prompts malignant transformation of the cervical epithelium. 36 , 37 , 38 , 39 For epithelial ovarian cancer, a disease including at least five histological subtypes and arising from fallopian tube fimbria, ovarian, and peritoneal surfaces, most recent studies have proven a relationship between increasing BMI and nonserous histologies.…”
Section: Obesity and Development Of Gynecologic Cancersmentioning
confidence: 99%
“…More recent studies analyzing specific histologies in these cancers have begun to establish this relationship with obesity. In cervical cancer, an increase in BMI has been associated with a higher risk of developing cervical adenocarcinoma 34,35 . Additionally, persistent cervical infection by high‐risk HPV strains is favored in obese women presenting vaginal dysbiosis, which is characterized by an increase in microbial diversity that prompts malignant transformation of the cervical epithelium 36–39 .…”
Section: Obesity and Development Of Gynecologic Cancersmentioning
confidence: 99%